"Book review". A theory of civil war - Javier Lion Bustillo (Revista CIDOB d'Afers Internacionals, 2022)
"Review of the book" Schulhofer-Wohl, Jonah. Quagmire in civil war. Cambridge University Press, 2020. 317 págs.